2019
DOI: 10.1002/14651858.cd000125.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Local opinion leaders: effects on professional practice and healthcare outcomes

Abstract: Background-Clinical practice is not always evidence-based and, therefore, may not optimise patient outcomes. Opinion leaders disseminating and implementing 'best evidence' is one method that holds promise as a strategy to bridge evidence-practice gaps. Objectives-To assess the effectiveness of the use of local opinion leaders in improving professional practice and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
164
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(181 citation statements)
references
References 129 publications
9
164
1
7
Order By: Relevance
“…A Cochrane review confirmed that opinion leaders can promote evidence-based practice and reported a 10.5% increase in compliance when used as a strategy [29]. However, several studies failed to identify and clearly describe the role of clinical opinion leaders, particularly in ambulatory care settings [29,30]. Physicians participating in this study only mentioned opinion leaders in their PCNs when asked general questions about PCNs management and scarcely regarding a rational use of antibiotics.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A Cochrane review confirmed that opinion leaders can promote evidence-based practice and reported a 10.5% increase in compliance when used as a strategy [29]. However, several studies failed to identify and clearly describe the role of clinical opinion leaders, particularly in ambulatory care settings [29,30]. Physicians participating in this study only mentioned opinion leaders in their PCNs when asked general questions about PCNs management and scarcely regarding a rational use of antibiotics.…”
Section: Discussionmentioning
confidence: 71%
“…This is particularly notable as opinion leaders are a frequently examined aspect of social networks and considered to be a strong influence on other network members as they seem to amplify dissemination of ideas and information [28]. A Cochrane review confirmed that opinion leaders can promote evidence-based practice and reported a 10.5% increase in compliance when used as a strategy [29]. However, several studies failed to identify and clearly describe the role of clinical opinion leaders, particularly in ambulatory care settings [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, academic detailing has potential to influence clinician behavior, especially if targeted to key opinion leaders who are perceived as influential experts by their peers. 21,27 Other evidence suggests that in decentralized networks, social influence can generate learning dynamics that improve the performance of the group, 28 which could potentially slow adoption of low-value therapies or those lacking sufficient evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review confirmed that opinion leaders can promote evidence-based practice and reported a 10.5% increase in compliance when used as a strategy [29]. However, several studies failed to identify and clearly describe the role of clinical opinion leaders, particularly in ambulatory care settings [29,30]. Physicians participating in this study only mentioned opinion leaders in their PCN when asked general questions about PCN management and scarcely regarding a rational use of antibiotics.…”
Section: Discussionmentioning
confidence: 72%